Handgrip Strength, Depression, Dementia, Cognitive Function, and Their Predictive Effect on Functional Independence in Older Adults - Juan Antonio Campos-Gutiérrez; Enrique Diaz De León-González; Hugo Gutiérrez Hermosillo; Ricardo M. Cerda; Georgina Mayela Núñez Rocha; Jorge Zamarripa; Ricardo López-García; Guillermo Cano-Verdugo; Rocío Martínez-Hernández (Medicina, 2025)
Background and Objectives: Globally, there is a demographic transition toward an increase in the number of older adults, and with it, the comorbidities associated with aging. This requires healthcare providers to understand which variables can affect functional independence for performing activities of daily living. The general objective of this study was to determine the predictive effect of left and right handgrip strength, depression, mild to moderate dementia, and cognitive function on functional independence in older adults. Materials and Methods: This study featured a predictive cross-sectional design with n = 84 older adults with some level of physical independence; older adults with completely limited physical independence and those with severe dementia were excluded. To assess depression, the Geriatric Depression Scale was used; for dementia, the Hachinski Ischemic Scale was used; for cognitive impairment, the Folstein version of the MMSE was used; for functional independence, the Barthel Index was used; for handgrip, a 90-kg Dynatron® professional hydraulic dynamometer (UT 84121) Number Series. 11010141, from the Dynatronics Corporation located in Salt Lake City, Utah USA, was used. Results: In total, 58.8% of the participants were female, with a mean age of 84.89 ± 7.095, with ranges from 68 to 102 years. Multiple regression analysis showed that the level of cognition, left-hand grip strength, and a low level of depression are strong predictors of independence in activities of daily living in the elderly, with an explained variance of R2 = 0.34. Conclusions: Cognitive function, left-hand grip strength, and depression significantly predict the independence of older adults. Studies with larger sample sizes are recommended to confirm the veracity of the results and to design methodologically rigorous interventions that include psychological aspects such as cognitive stimulation, promoting physical activity, and addressing depressive problems to improve the functional independence of older adults.